STRATEGI BISNIS ANGKRINGAN KOPI JOSS SEBAGAI PENDUKUNG PARIWISATA KOTA YOGYAKARTA SELAMA PANDEMI COVID-19 - Dyah Wahyuning Tyas; Haritsah Kusumaningrum; Pipin Kusumawati; Harits Dwi Wiratma (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
This study identifies internal and external factors to determine the strategy used by angkringan stalls in an effort to survive during the Covid-19 pandemic and support tourism and improve the welfare of sellers. This research method uses a quantitative descriptive SWOT analysis based on primary data from interviews and questionnaires by random sampling. The results of the analysis of the SWOT matrix strategy formulation found that the highest order priority occurs in the Strengths – Opportunities condition (3.5589). Strengths – Opportunities strategy can maximize strengths and take advantage of opportunities so that the Cartesian quadrant direction supports an aggressive growth strategy and angkringan has the potential to grow and develop as a tourism support business.